Fundamentando a matemática utilizada por pedreiros de icapuí-ce na construção de uma residência - Silva, Tonicley Luís da (Universidade Federal Rural do Semi-Árido, 2019)
This study aims to investigate the formal mathematical knowledge of the domain used by masons to build a residence in the community of Placa - Icapuí-CE. In this sense, we intend to understand what is Ethnomathematics and its assumptions and also the Ethnomathematics ratio used by masons on the job and understand the processes are used in practice to calculate and measure during the construction. To achieve the objectives, was made use of theoretical and D'AMBRÓSIO (2005) PIRES (2005) among others, and also field research through on-site observation, notes and verification of mathematical Mason practice and the formal school mathematics, and so, realize the importance of cultural knowledge of mathematics by professionals who have acquired over time. The research discusses the ethnomathematical knowledge and importance of this knowledge when building a residence
Keywords: Etnomatemática; Pedreiro; Conhecimento; Matemática; Construção; Ethnomathematical.; Mason; Knowledge; Mathematic; Construction; CIENCIAS EXATAS E DA TERRA::MATEMATICA